Genetic Ablation of the Platelet Activating Factor Receptor Does Not Impair Learning and Memory in Wild-Type Mice or Alter Amyloid Plaque Number in a Transgenic Model of Alzheimer’s Disease - Peshdary, Vian (Université d'Ottawa / University of Ottawa, 2012)
We have recently established that aberrant alkylacylglycerophosphocholine metabolism results in the increased tissue concentration of platelet activating factors (PAFs) in the temporal cortex of Alzheimer Disease (AD) patients and in TgCRND8 mice over-expressing mutant human amyloid precursor protein. PAF lipids activate a G-protein coupled receptor (PAFR) reported to be expressed by microglia and subsets of neurons in rat. It is not known whether this same expression pattern is recapitulated in mice however, as the expression has only been inferred by use of pharmacological PAFR antagonists, many of which impact on both PAFR-dependent and PAFR-independent signalling pathways. PAFR plays a role in long term potentiation (LTP) induction in rats. PAFR has also been implicated in behavioural indices of spatial learning and memory in rats. Contradictory reports using mice provide ambiguity regarding the role of PAFR in LTP induction in mice. To assess whether PAFR is expressed in murine neurons, I localized PAFR mRNA in wild-type C57BL/6 mice using PAFR KO mice as a negative control. I further showed that the loss of PAFR did not impair learning and memory although this assessment must be considered preliminary as the behavioural test employed was not optimized to detect changes in learning and memory of C57BL/6 mice over time adequately.Finally, I showed that the loss of PAFR in TgCRND8 mouse model of AD had no impact upon Aβ plaque number. My observations suggest that PAFR is restricted to microglial-like cells in mouse hippocampus and as such, it may not play a role in learning and memory.
Keywords: amyloid beta plaque; Alzheimer's disease; long term potentiation; platelet activating factor receptor; learning and memory